The Mediating Role of Business Development Competence in the Relationship Between Formal and Non-Formal Entrepreneurship Education on MSMEs Performance in Makassar, Indonesia - Bahrul ulum Ilham; Badaruddin; Mariah; Sugeng Susanto (Universitas Pendidikan Ganesha, 2026)
This study aims to analyze the influence of formal and non-formal entrepreneurship education on business performance, with business development competence as a mediating variable. The research was conducted with 100 MSME entrepreneurs in Makassar City, Indonesia, using a quantitative approach through surveys and Structural Equation Modeling-Partial Least Squares (SEM-PLS) data analysis. The results indicate that formal education has a significant effect on business development competence (β = 0.295; p < 0.05) but does not directly affect business performance (β = -0.008; p > 0.05). In contrast, non-formal education positively affects both business development competence (β = 0.263; p < 0.05) and business performance directly (β = 0.176; p < 0.05). Business development competence serves as a significant mediator between both formal and non-formal education and business performance, with mediation effects of β = 0.169 and β = 0.151, respectively. These findings underscore the critical synergy between formal education and non-formal training in building entrepreneurial competencies that enhance business outcomes. This study extends competence-based entrepreneurship theory by demonstrating that formal entrepreneurship education influences MSMEs' performance only through competence accumulation. At the same time, non-formal training operates through both direct and indirect pathways. By disentangling these learning modalities, the findings challenge the assumption of a universal education–performance link and offer new empirical insights from an emerging economy context. The study contributes to the theoretical discourse on entrepreneurial learning and offers practical recommendations for policymakers and educational institutions to design more integrative and application-oriented entrepreneurship programs.